2006
DOI: 10.1007/s00253-005-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a new Mycobacterium austroafricanum strain, IFP 2015, growing on MTBE

Abstract: A new Mycobacterium austroafricanum strain, IFP 2015, growing on methyl tert-butyl ether (MTBE) as a sole carbon source was isolated from an MTBE-degrading microcosm inoculated with drain water of an MTBE-supplemented gasoline storage tank. M. austroafricanum IFP 2015 was able to grow on tert-butyl formate, tert-butyl alcohol (TBA) and alpha-hydroxyisobutyrate. 2-Methyl-1,2-propanediol was identified as the TBA oxidation product in M. austroafricanum IFP 2015 and in the previously isolated M. austroafricanum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…The MTBE biodegradation pathway of M. austroafricanum IFP 2012 has been partially characterized by identifying several degradation intermediates, such as tert-butyl alcohol (TBA), which frequently accumulates in aquifers contaminated by MTBE (François et al, 2002). We recently detected 2-methyl 1,2-propanediol (2-M1,2-PD) as the product of TBA oxidation in M. austroafricanum IFP 2012and IFP 2015(Lopes Ferreira et al, 2005, and demonstrated its transformation to 2-hydroxyisobutyric acid (HIBA) in resting-cell experiments. 2-Methyl 1,2-propanediol (2-M1,2-PD) has been reported by Steffan et al (1997), using propane-oxidizing bacteria able to degrade MTBE by cometabolism, and by Smith et al (2003), using Mycobacterium vaccae JOB5 as the product of TBA degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTBE biodegradation pathway of M. austroafricanum IFP 2012 has been partially characterized by identifying several degradation intermediates, such as tert-butyl alcohol (TBA), which frequently accumulates in aquifers contaminated by MTBE (François et al, 2002). We recently detected 2-methyl 1,2-propanediol (2-M1,2-PD) as the product of TBA oxidation in M. austroafricanum IFP 2012and IFP 2015(Lopes Ferreira et al, 2005, and demonstrated its transformation to 2-hydroxyisobutyric acid (HIBA) in resting-cell experiments. 2-Methyl 1,2-propanediol (2-M1,2-PD) has been reported by Steffan et al (1997), using propane-oxidizing bacteria able to degrade MTBE by cometabolism, and by Smith et al (2003), using Mycobacterium vaccae JOB5 as the product of TBA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other strains able to grow in the presence of MTBE have been isolated from different environments: strain UC1, closely related to R. gelatinosus PM1, and UC3, closely related to M. austroafricanum IFP 2012, were isolated from an MTBE-degrading biofilter (Pruden & Suidan, 2004); strain L108 was isolated from an MTBEcontaminated aquifer in Germany (Rohwerder et al, 2004); and M. austroafricanum IFP 2015 was isolated from the drain water of an MTBE-supplemented gasoline storage tank (Lopes Ferreira et al, 2005). The MTBE biodegradation pathway of M. austroafricanum IFP 2012 has been partially characterized by identifying several degradation intermediates, such as tert-butyl alcohol (TBA), which frequently accumulates in aquifers contaminated by MTBE (François et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a few strains were able to grow on MTBE and therefore on TBA; Methylibium petroleiphilum PM1 (Hanson et al 1999;Nakatsu et al 2006), Hydrogenophaga flava ENV735 (Hatzinger et al 2001), M. austroafricanum IFP 2012 (François et al 2002) and, more recently, M. austroafricanum IFP 2015 (Lopes Ferreira et al 2006b) and Aquincola tertiaricarbonis L10 (Lechner et al 2007). These strains have been studied at the physiological level, but the genes and enzymes involved in the oxidation of MTBE and in the oxidation of TBA are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Both MTBE and TBA were inducers of MTBE and TBA degradation activity (François et al 2002). More recently, M. austroafricanum IFP 2015 was isolated for its capacity to grow on MTBE (Lopes Ferreira et al 2006b). The product of TBA oxidation, 2-methyl 1,2-propanediol (2M1,2PD), was identified during the oxidation of TBA by resting cells of M. austroafricanum IFP 2012 and IFP 2015; the conversion of 2M1,2PD to hydoxisobutyric acid (HIBA) was also shown (Lopes Ferreira et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation